Determinants of Payout Policy and Investment Attractiveness of Companies Listed on the Warsaw Stock Exchange - Aleksandra Pieloch-Babiarz (Institute of Economic Research (IER), 2017)
Making decisions concerning the payout policy depends on many diversified neoclassical and behavioral determinants. Although these factors are well-described in the literature, there is still a research gap concerning the lack of a comprehensive impact model of payout policy determinants on the investment attractiveness of shares. The aim of this paper is to present the diverse nature of relationships between different forms of cash transfer to the shareholders and investments attractiveness of public companies in the context of determinants of payout policy. The possibility to achieve this objective was conditioned by empirical verification of research hypothesis stating that the diversify of payout forms is accompanied by the different determinants of payout policy which condition an effective investment of stock investors capital. The empirical research was conducted on the electromechanical companies which were listed on the Warsaw Stock Exchange in years 2006-2015. The data for analysis were mainly collected from database Notoria Service SA and Stock Exchange Yearbooks. The calculations were carried out using the methodology of taxonomic measure of investment attractiveness, as well as dividend premium and share repurchase premium. The final conclusion of our research is that the companies conducting the payout policy in different forms of cash transfer differ in terms of many characteristics, such as: financial standing, market value, ownership structure, company's size and age. Moreover, their investment attractiveness differs according to regularity of payment, stock exchange situation and shareholders preferences. The value added of this paper is a new approach to the evaluation of capital investment with a special emphasis on the determinants of payout policy.
Keywords: G02; G10; G35; 330; determinants of payout policy; investment attractiveness; dividend; share repurchase